Quantifying sources of increasing zinc from acid rock drainage in an alpine catchment under a changing hydrologic regime. Issue 5 (11th February 2013) - Crouch, Caitlin M.; McKnight, Diane M.; Todd, Andrew S.; Tetzlaff, Doerthe; Carey, Sean; Soulsby, Chris
Abstract A major water quality concern in the Rocky Mountains is acid rock drainage (ARD), which causes acidic conditions and high metal concentrations in streams. The 30‐year water quality record for the upper Snake River in Colorado, USA, shows that summer low‐flow zinc concentrations have increased four‐ to sixfold concurrently with increases in mean annual and summer temperatures and a two‐ to three‐week advancement in spring snowmelt. We found that the main source of zinc and other metal loads to the upper Snake River was a tributary draining an alpine area rich in disseminated pyrite. By conducting a tracer experiment in this tributary of interest, we demonstrated that 30% of the trace metal loading entered in an upper steep, rocky reach where the tributary of interest is fed by an alpine spring. Another increase in flow and metal loading occurred where the tributary of interest flows through a gently sloped wetland area. Analysis of the tracer experiment indicated a significant increase in hyporheic exchange along this wetland reach, from which metals appear to be mobilized. Several potential explanations are presented that might explain this phenomenon: decreasing pH in the tributary of interest may result in mobilization of metals from the wetland and hyporheic zone; the geochemistry of groundwater inflows to the wetland may be changing; and, wetland soils may be drying out with longer, warmer summers. This study illustrates how changes in hydrologic regime may cause changes in biogeochemical processes that exacerbate the danger to aquatic ecosystems associated with ARD. Copyright © 2012 John Wiley & Sons, Ltd.